Body Image Determinants for Teenagers Aged 12-16 Years - Ade Saputra Nasution; Ida Nuraida; Warini Warini; Wawan Gunawan (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The problem that arises in teenagers today is body image or body image, where body image is a very important and important thing for teenagers because the appearance of the shape and size of a teenager's body can increase self-confidence if they have a positive body image or are satisfied, but on the contrary, teenagers who have Negative or dissatisfied body image will have a negative impact on self-confidence and teenagers health such as bulimia, anorexia, malnutrition and obesity. Teenagers who have a body shape that is not ideal (thin or obese) are more likely to feel negative perceptions, this will have an impact on the mental health and development of teenagers. The aim of this study is to analyze the determinants (nutritional status, food availability, and sleep duration) of body image of teenagers aged 12-16 years. The method used in this study was cross-sectional with a sample of 57 teenagerss aged 12-16 years taken by random sampling and data obtained using a questionnaire and then analyzed using the chi-square test to see the relationship between the independent variable (nutritional status, food availability, and sleep duration) and the dependent variable (body image). The nutritional status variable (0.004) describes a relationship with body image, food availability (1,000) illustrates that there is no relationship with teenagers body image, while sleep duration(1,000) illustrates that there is no relationship with teenagers body image. It is necessary to suggest a promotional or educational effort for teenagers to increase nutritional knowledge so that it can improve nutritional status in teenagers and will be able to increase positive perceptions of body image in teenagers. Keyword: Body Image, Food Availability, Nutritional Status, Sleep Duration, Teenagers